A Novel Bioimpedance-Based Detection of Miltefosine Susceptibility Among Clinical Leishmania donovani Isolates of the Indian Subcontinent Exhibiting Resistance to Multiple Drugs - Ghosh, Souradeepa; Biswas, Souvik; Mukherjee, Sandip; Pal, Arijit; Saxena, Aaditya; Sundar, Shyam; Dujardin, Jean-Claude; Das, Soumen; Roy, Syamal; Mukhopadhyay, Rupkatha; Mukherjee, Budhaditya (Frontiers in Cellular and Infection Microbiology, 2021)
The extent of susceptibility towards Miltefosine (Mil), Amphotericin B (AmpB), and Paromomycin (Paro) were measured among nineteen clinical isolates of Leishmania donovani (LD). Thirteen of these clinical isolates were reported to exhibit low susceptibility towards Sodium stibogluconate (SSG-R) while six of them were highly susceptible(SSG-S). The degree of clearance of amastigotes (EC50) for these predefined SSG-R and SSG-S-infected macrophages were determined against Mil, AmpB, and Paro. 2 out of the 13 SSG-R isolates (BHU575, BHU814) showed low susceptibility towards all three drugs studied, while the rest of the eleven SSG-R isolates showed varying degree of susceptibility either towards none or only towards individual drugs. Interestingly, all the SSG-S isolates showed high susceptibility towards Mil/AmpB/Paro. The total intracellular non-protein thiol content of the LD-promastigotes, which has been previously reported to be positively co-related with EC50 towards SSG, was found to be independent from the degree of susceptibility towards Mil/ AmpB/ Paro. Impedance spectra analysis, which quantifies membrane resistance, revealed lower impedimetric values for all those isolates exhibiting low efficacies to Mil (Mil-R). Our analysis points out that while non-protein thiol content can be an attribute of SSG-R, lower impedimetric values can be linked with lower Mil-susceptibility, although neither of these parameters seems to get influenced by degree of susceptibility towards AmpB/Paro. Finally, correlation analysis with established biological methods suggests that impedance spectral analysis can be used for accurate determination of lower Mil-susceptibility among LD isolates which is further validated in the LD-infected in vivo hamster model.